STRATEGIC FRAMEWORK FOR ENHANCING ACADEMIC EXCELLENCE: AN IN-DEPTH EXAMINATION OF FACULTY DEVELOPMENT INITIATIVES IN INSTITUTIONS OF HIGHER EDUCATION - Jalal Karim, Akram (International Journal of Teaching and Learning, 2024)
This study observes the pivotal role of Strategic Planning Efforts (SPEs) and their influence on enhancing teaching and learning products, as well as exploring the essential role of Faculty Development Programs (FDPs) in boosting the quality and level of education and learning within HEIs. The main outcomes of the FDPs that serve as pillars of teaching and learning and that are adopted in this paper as basic criteria for the proposed conceptual framework are: Pedagogical Contents Knowledge (PCK), Curriculum Development and Course Design (CDCD), Instructional Skills (ISs), Enhanced Assessment and Feedback Practices (EAFP), and Professional Growth and Reflection (PGR). The surveys were used as a research method, and the questionnaire was sent to selected experts in the field of academic development programs, faculty, and administrators in HEIs in Iraq, and analysed using SPSS software. The results revealed a strong positive impact of Strategic Planning in activating Academic Development Programs, and a strong impact of Academic Development Programs on strengthening the main pillars of teaching and learning stated in the study.